2019
DOI: 10.1177/1836939119885305
|View full text |Cite
|
Sign up to set email alerts
|

The status-quo of play-based pedagogies in Western Australia: Reflections of early childhood education practitioners

Abstract: This paper discusses the findings of a qualitative research project conducted in 2017 that explored practitioners’ experiences and perceptions of the provision of play pedagogies in contemporary Western Australian early childhood education contexts. Interviews were conducted with four play-based learning teachers and an open-ended survey was completed by 40 early childhood educators who were members of the audience at a Western Australia conference in 2017. The study participants discussed beliefs and values p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 17 publications
(27 reference statements)
0
5
0
2
Order By: Relevance
“…This poses a challenge for early years teachers when the principals’ direction for practice and pedagogy goes against their own (Roberts-Holmes & Bradbury, 2016). In a study by Barblett et al (2016), teachers reported being expected to ‘teach in ways that clashed with their philosophical beliefs and did not allow for play-based learning’ (p. 40) when principals did not have early childhood knowledge. Hesterman and Targowska (2020) similarly found teachers believed principals’ lack of early childhood knowledge inhibited their ability to implement the EYLF (DEEWR, 2009), particularly play-based learning.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This poses a challenge for early years teachers when the principals’ direction for practice and pedagogy goes against their own (Roberts-Holmes & Bradbury, 2016). In a study by Barblett et al (2016), teachers reported being expected to ‘teach in ways that clashed with their philosophical beliefs and did not allow for play-based learning’ (p. 40) when principals did not have early childhood knowledge. Hesterman and Targowska (2020) similarly found teachers believed principals’ lack of early childhood knowledge inhibited their ability to implement the EYLF (DEEWR, 2009), particularly play-based learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alongside this is the introduction of ability grouping, and low ‘performing’ children being labelled as ‘hopeless cases’ (p. 126) or as having additional learning needs to protect teachers from scrutiny (Roberts-Holmes & Bradbury, 2016). In Australia, the pushed down curriculum and expectations for academic achievement has led to a decrease in play based pedagogies (Barblett et al, 2016; Hesterman & Targowska, 2020), with teachers also reporting limiting children’s contributions to the curriculum (Leggett & Ford, 2013). High-stakes testing such as NAPLAN also imposes on pedagogy with reports that teachers spend more time on subjects that are assessed (Roberts et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Perencanaan pembelajaran meliputi penyusunan rencana pelaksanaan pembelajaran dan penyiapan media dan sumber belajar, perangkat penilaian pembelajaran, dan skenario pembelajaran (Hakkarainen, 2008;Ward, 2018). Perangkat pembelajaran menjadi salah satu hal penting untuk menunjang keberhasilan pelaksanaan aktivitas pembelajaran (Antara, 2018;Darling-Hammond et al, 2020;Hesterman & Targowska, 2020;Meilani & Faradiba, 2019;Møller-Skau & Lindstøl, 2022), oleh karena itu harus mendapat perhatian untuk dipersiapkan dengan baik oleh guru. Perangkat pembelajaran yang diperlukan dalam mengelola proses belajar mengajar dapat berupa silabus, RPP dan lembar aktivitas siswa.…”
Section: Pendahuluanunclassified
“…Competing views of practitioners, mistranslation of the EYLF into practice and historic views of play and learning have all contributed to the neglect of intentionality in pedagogy (i.e. monitoring, planning for and scaffolding learning; Edwards & Cutter-Mackenzie, 2011; Hesterman & Targowska, 2020; Kilderry, 2015).…”
Section: Introductionmentioning
confidence: 99%